Does Economic Diversification Lead to Financial Development? : Evidence From topography - Ramcharan, Rodney (IMF Working Papers; Working Paper ;, 2006)
An influential theoretical literature has observed that economic diversification can reduce risk and increase financial development. But causality operates in both directions, as a well functioning financial system can enable a society to invest in more productive but risky projects, thereby determining the degree of economic diversification. Thus, ordinary least squares (OLS) estimates of the impact of economic diversification on financial development are likely to be biased. Motivated by the economic geography literature, this paper uses instruments derived from topographical characteristics to estimate the impact of economic diversification on the development of finance. The fourth estimates suggest a large and robust role for diversification in shaping financial development. And these results imply that, by impeding financial sector development, the concentration of economic activity common in developing countries can adversely affect financial and economic development.